The social value of drug addicts: uses of the useless - Singer, Merrill (Routledge, Taylor & Francis Group, 2016)
"Drug users are typically portrayed as worthless slackers, burdens on society, and just plain useless--culturally, morally, and economically. By contrast, this book argues that the social construction of some people as useless is in fact extremely useful to other people. Leading medical anthropologists Merrill Singer and J. Bryan Page analyze media representations, drug policy, and underlying social structures to show what industries and social sectors benefit from the criminalization, demonization, and even popular glamorization of addicts. Synthesizing a broad range of key literature and advancing innovative arguments about the social construction of drug users and their role in contemporary society, this book is an important contribution to public health, medical anthropology, popular culture, and related fields"--